Discovery Nusantara Creative Dance Creation Training as a Platform for Talent Development and Social Therapy for Inmates at Kerobokan Women's Prison - Agustawan, Dewa Made; Putra, I Gede Gunadi; Widyastuti, Ida Ayu Gede Sasrani (Outline Publisher, 2025)
This community service activity aims to provide training in creating the creative dance